POLLEN FROM SURFACE SAMPLES AS AN ENVIRONMENTAL INDICATOR - Dzyuba O.F. (My University, 2006)
Palynological analysis of surface samples was accomplished within the framework of integrated ecological investigation of northwestern Timan-Pechora oil-and-gas-bearing province (sampling depth, 0.015 m). Palynological results corroborated geochemical conclusions and allow the author to suggest that this area is gametopathogenically hazardous. This hypothesis is supported by the peculiarities of teratomorphic pollen grains found in the surface samples. © Pleiades Publishing, Inc. 2006.
Keywords: ENVIRONMENTAL INDICATOR; PALYNOLOGICAL ANALYSIS; TERATOMORPHOSIS; TIMAN-PECHORA PROVINCE